Patterns of persistent poverty: Evidence from EU-SILC - Stephen Jenkins; Philippe van Kerm (University of Essex, Institute for Social and Economic Research (ISER), 2011)
The persistent at-risk-of-poverty rate is one of the EU's 11 primary indicators of social inclusion but it has received little attention compared to the current at-risk-of-poverty rate. Using the 2008 EU Statistics on Income and Living Conditions (EU-SILC) database, we compare persistent income poverty rates across European nations and examine differences in poverty profiles for subgroups defined by age and sex. We draw attention to similarities between the profiles for persistent at-risk-of-poverty rates and at-risk-of-poverty rates, and are led to question the relevance of the former measure in its current form as a key EUindicator of social progress.
Keywords: I32; D31; 330; persistent poverty; income poverty; poverty; EU-SILC; Europe